Characterization of cDNAs encoding human pyruvate dehydrogenase alpha subunit. - Ho, L (1989)
A cDNA clone (1423 base pairs) comprising the entire coding region of the precursor form of the alpha subunit of pyruvate dehydrogenase (E1 alpha) has been isolated from a human liver cDNA library in phage lambda gt11. The first 29 amino acids deduced from the open reading frame correspond to a typical mitochondrial targeting leader sequence. The remaining 361 amino acids, starting at the N terminus with phenylalanine, represent the mature mitochondrial E1 alpha peptide. The cDNA has 43 base pairs in the 5' untranslated region and 210 base pairs in the 3' untranslated region, including a polyadenylylation signal and a short poly(A) tract. The nucleotide sequence of human liver E1 alpha cDNA was confirmed by the nucleotide sequences of three overlapping fragments generated from human liver and fibroblast RNA by reverse transcription and DNA amplification by the polymerase chain reaction. This consensus nucleotide sequence of human liver E1 alpha cDNA resolves existing discrepancies among three previously reported human E1 alpha cDNAs and provides the unambiguous reference sequence needed for the characterization of genetic mutations in pyruvate dehydrogenase-deficient patients.